Sejarah Perkembangan Marga Lembak Tahun 1950-1984 - Oktasyawitri, Endah Sulistia; Irwanto, Dedi (Riwayat: Educational Journal of History and Humanities, 2025)
This study, titled "The Historical Development of the Lembak Clan from 1950 to 1984", aims to examine the changes in traditional governance structures, the socio-economic conditions of the clan community, and the impact of national policy on local systems during the period of 19501984. The research employs a historical method, including heuristic steps, source criticism, interpretation, and historiography. Data were collected through literature review and interviews. The study uses political, economic, social, and anthropological approaches. The findings reveal that the Lembak Clan was governed by a et al , who held executive, legislative, and judicial powers. In practice, the system also regulated the social, economic, and cultural life of the community, including traditions such as marhaba, sedekah bedusun, and communal work (gotong royong). Major changes occurred with the implementation of Law No. 5 of 1979, which abolished the marga system and replaced it with a village-based administration. This led to institutional restructuring, shifts in the roles of traditional leaders, and the loss of local authority over resource management. Nevertheless, some traditions and cultural values of the Lembak people have been preserved through the continued role of customary leaders.